MEMBANGUN EKONOMI KELUARGA DENGAN BISNIS SYARIAH MELALUI HALAL NETWORK INTERNASIONAL - Mawardi, Mawardi; Ruslaini, Ruslaini (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2023)
Sharia business is a business activity that is developed according to the rules stated in the Al-Quran and Hadith. In order to be called a sharia business or business, all aspects of the activity must apply sharia principles. In running a sharia business, HNI has an important program in building the family economy. The formulation of the research problem is (1). How is the HNI program in building the economy? (2) What are the HNI sharia business opportunities in building the family economy? This field research descriptive in nature, with data collection through interviews with related parties, observations of the environment and documentation data conducted through official HNI websites, education through on-line and off-line broadcasts. The results of the study found that in building the family economy it was carried out with 4 programs (1) inviting lifestyle changes to halal products, (2) empowering family health and family economy (3) allocating funds for product promotion in Asia and the world, (4) ) provides businesses that meet the criteria as businesses that are in great demand today. HNI opens the widest possible opportunities for everyone, the same opportunities as well as opportunities for success in building the family economy.